Inhibition of Migration of SW-480 Cells Induced by Royal Jelly Due to Reduction of β-Catenin - Milena Jovanović; Dragana Šeklić (Biology and Life Sciences Forum)
Royal jelly (RJ), a natural bee product known for its abundance of bioactive compounds, is often referred to as a “superfood” and has been utilized in alternative medicine for centuries. Numerous studies have highlighted its therapeutic properties, including anticancer activity. A major challenge in standard cancer therapy is the migration of cancer cells, which leads to metastasis and the formation of secondary tumors with often fatal outcomes. Cancer cell migration is facilitated by the epithelial-to-mesenchymal transition (EMT) and the aberrant activation of the Wnt/β-catenin signaling pathway. A key component of this pathway, the transcription factor β-catenin, regulates the expression of various cellular components that play critical roles in cell motility. This study investigated the antimigratory potential of RJ on the colorectal cancer cell line SW-480 and its effects on β-catenin protein expression. RJ significantly suppressed the motility of SW-480 cells and markedly reduced β-catenin protein levels 24 h after treatment. These findings underscore the potential of RJ as a functional food to regulate colorectal cancer cell motility through modulation of β-catenin, thereby reducing disease aggressiveness.